Qualitative and Quantitative Paradigm Constellation In Educational Research Methodology - Djafar, Hilman; Yunus, Rasid; DJ Pomalato, Sarson W; Rasid, Ruslan (International Journal of Educational Research & Social Sciences, 2021)
Differences qualitative and quantitative research to academicians and researchers mainly concentrated on education studies is only able to browse and identify with the fundamental difference merely as example: research that only uses quantitative data but using the qualitative as a benchmark often not considered as a quantitative research Likewise , qualitative research that uses quantitative data is not considered qualitative research. If traced further, actually qualitative and quantitative research very spacious and is a level. Qualitative and quantitative research in the context of methodology includes a researcher's conception of social reality, the researcher's self placement in relation to the reality study and various other reviews. Therefore, in this research article,is stated that the correlation between qualitative and quantitative research in educational research methodology is possible if both are based on the same paradigm. Conversely qualitative and quantitative researchis difficult to reconcile if they depart from different paradigms, which have different epistemological assumptions, and different goodness criteria.